2014
DOI: 10.1513/annalsats.201308-277oc
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual Microcirculation in Pulmonary Arterial Hypertension

Abstract: Patients with PAH showed lower sublingual microvasculature flow index and higher tortuosity compared with healthy age- and sex-matched control subjects. Further investigations are needed to assess whether this methodology can provide information on disease prognosis and/or response to therapy in this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 47 publications
3
32
0
Order By: Relevance
“…Initial studies characterized idiopathic PAH (IPAH) as a disease of the pulmonary circulation; however, recent data from us (2,3) and other investigators (4)(5)(6) showed evidence of extrapulmonary vascular involvement.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Initial studies characterized idiopathic PAH (IPAH) as a disease of the pulmonary circulation; however, recent data from us (2,3) and other investigators (4)(5)(6) showed evidence of extrapulmonary vascular involvement.…”
Section: To the Editormentioning
confidence: 99%
“…However, patients with specific asthma phenotypes might benefit from FE NO monitoring. In particular, in patients with "discordant phenotypes" (high inflammation, low symptoms or high symptoms, low inflammation), an inflammation-driven strategy might be beneficial (2). The aim of our study was (1) to assess the presence and stability of concordant and discordant asthma phenotypes in children and (2) to assess whether children with a discordant phenotype were more likely to benefit from adjusting treatment to FE NO than children with a concordant phenotype.…”
Section: To the Editormentioning
confidence: 99%
“…Assessment of microvascular hemodynamics has been reported in non-ocular tissues, including nail fold [29], sublingual [30], and buccal mucosa [31] with the use of CapiScope, a commercially available device. Although, this device is capable of automated blood vessel diameter measurements, evaluation of blood velocity requires manual drawing of a line along a target vessel.…”
Section: Discussionmentioning
confidence: 99%
“…We tested this noninvasive methodology in patients with PAH, a condition that with time leads to decrease cardiac output and poor peripheral perfusion. In addition, there is mounting evidence that PAH is not only a disease limited to pulmonary vasculature but also affects the systemic microcirculation [4,14]. Hofstee et al found that a reduction in nailfold capillary density was associated with PAH severity in patients with systemic sclerosis or idiopathic PAH[14].…”
Section: Discussionmentioning
confidence: 99%